Influence of MoS2 and graphite-reinforced nanofluid-MQL on surface roughness, tool wear, cutting temperature and microhardness in machining of Inconel 625. (April 2023) - Makhesana, Mayur A.; Patel, Kaushik M.; Krolczyk, Grzegorz M.; Danish, Mohd; Singla, Anil Kumar; Khanna, Navneet
Abstract: The machinability of nickel-based alloys is affected by the amount of friction and heat produced through machining. The usage of metalworking fluids raises concerns about the operator's health and environmental impact. Therefore, minimum quantity lubrication (MQL) is preferred as one of the cooling/lubrication alternatives to achieve enhanced machining performance. The effectiveness of MQL application can be enhanced by using vegetable oil blended with nanoparticles. Considering these facts, the machinability of Inconel 625 is assessed using varying concentrations (0.5%, 1%, 1.5%, and 2%) of graphite and molybdenum disulfide (MoS2 ) nanoparticles in sunflower oil. The tribological and thermophysical properties of prepared nanofluids in the form of friction coefficient, thermal conductivity, and dynamic viscosity are evaluated. The turning tests are conducted under dry, MQL, and nanofluid-MQL (nMQL) environments, and the findings are compared considering surface roughness, chip morphology, tool wear, cutting temperature, power consumption, and microhardness. The sunflower oil blended with MoS2 resulted in 56%, 42%, and 22% improved surface quality compared to dry, MQL, and nMQL (Graphite) conditions. Also, the efficacy of nMQL with graphite and MoS2 is seen in the form of slower tool wear progression. Also, MQL, nMQL with MoS2, and nMQL (Graphite) resulted in lower cutting temperatures by 18%, 35%, and 25%, respectively, compared to dry turning. The effective performance of nMQL is credited to the better penetration ability of the applied lubricant into machining interfaces. Furthermore, the MQL application with compressed air facilitated chip removal and heat dissipation during machining. Finally, the sustainability assessment through the Pugh matrix showcased the potential of nanofluid-MQL for machinability improvement of Inconel 625. Highlights: Analysis of friction coefficient and thermo-physical properties of nanofluids with different concentrations nanoparticles. Turning of Inconel 625 under dry, MQL, and nMQL (nanoparticles dispersed in vegetable oil) conditions were performed. Machinability indicators such as surface roughness, tool wear, chip morphology was improved with vegetable oil-based nMQL. Improved machining performance with vegetable oil was achieved with lower cutting temperature and energy consumption.